Seismic source of the 1966 Huacho-Peru 8.1 Mw earthquake from tsunami waveform in-version - Jiménez, C. (2017)
On October 17, 1966 at 21:41 UTC, a big earthquake shooked the central region of Peru, causing 100 deaths. The maximum severity of shaking was reported in the Huacho city (VIII-IX MM). As coseismic eﬀect a tsunami was generated, which ﬂooded some villages and beach resorts, as Casma and Tortugas. From analysis and signal processing of three tidal records observed at stations of Chimbote, Callao and Marcona, we determined the parameters of the seismic source through an inversion process, in which the computed signal is compared with the observed signal by a non-negative least square process. The maximum slip is 4.7 m and is located in the Southern side of rupture geometry, which means that the maximum asperity or zone of greatest energy release is located under the Ocean in front of the Huacho city, this is consistent with the maximum intensity values reported. The scalar tsunami moment is M0 = 1.76 × 1021 Nm, equivalent to a magnitude of 8.1 Mw.